OTOMATISASI PEMBAHARUIAN IP PADA DOMAIN ITICMALANG.NO-IP.ORG UNTUK AKASES GATEWAY DI PT.INDONESIAN TOBACCO - Rony Syafrudin, Achmad; Duty Susilo, Antonius; Yunus, Mahmud (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
The need for access to data across the network has now become one of the primary needs PT. Indonesian Tobacco.Purposes of data access can be realized if the company has a public IP functioned to access internal applications, vpn and cctv. The problem occurs because the public IP obtained from the internet provider is dynamic (always changing) so the impact on the configuration of the client-side gateway.the method that implemented is to change the public IP address to a fixed domain, the domain used is a domain that is free with no-ip.org with address iticmalang.no-ip.org. Configuration is configured in the router includes a domain update script and scheduler, if the public IP changes and scheduler are met then the router will request to change the IP domain domain with a public IP configured on the routerÂ Key words : mikrotic, CCTV, VPN, domain, gateway